Levels of metals and toxicity in sediments from a Ramsar site influenced by former mining activities - Feitosa Cruz, Ana Carolina [UNESP]; Gusso-Choueri, Paloma [UNESP]; Araujo, Giuliana Seraphim de; Campos, Bruno Galvao [UNESP]; Sousa Abessa, Denis Moledo de [UNESP] (Elsevier B.V., 2019)
This study aimed to evaluate the sediment quality in a Ramsar site located in the Southeast Brazil, by using several lines of evidence (LOEs). Chemical and sedimentological analyses, ecotoxicological tests, and whole sediment Toxicity Identification Evaluation (TIE) were performed. The sediments were predominantly composed of fine sands and muds. Higher concentrations of metals in the sediments collected close to Iguape were observed; however according to the SEM/AVS analyses, most sediments should not be toxic and the potentially toxic samples could occur along the whole channel. In fact, sediments of most stations were toxic in at least one survey. The PCA revealed associations between mud, metals and toxicity. Acutely toxic sediments presented Pb concentrations above the threshold effect levels, while chronic toxicity seemed to be influenced also by SEM. The most contaminated and toxic areas are not necessarily those located close to the primary sources, but are actually those with finer sediments. Toxicity Identification and Evaluation (TIE) showed that metals and ammonia were responsible for the toxicity. The results suggest that metals from former mining areas located at the upper Ribeira de Iguape River are transported to the Cananeia Iguape Peruibe Protected Area and accumulate in the sediments at potentially toxic levels. The location of muddy and more contaminated sediments appears to move along the estuary, accompanying the displacement of the maximum turbidity zone, which, in turn, depends on seasonal freshwater inputs. The results also showed that using several lines of evidences to asses contamination in a protected area provides reliable information to subsidise further actions to control the sources of contaminants.
Keywords: Ecotoxicology; Contamination; TIE; Marine protected areas; Estuary; Sediment